Cultura digital e a questão das gerações: uma abordagem através da Teoria Ator-Rede - LARI, José Otávio Pinheiro (2019)
The objective of this work is to map the process of consolidation of digital technology into a cultural phenomenon. Using the Actor-Network Theory, the text seeks to understand the path traveled by humanity to the digital culture and how the profound changes brought by this new way of being and acting in the world interfere in its own characterization as human and in its society. Two points of support are drawn in the work: the first is the concept of culture, foundation, and mark of the human species; the second is the question of generations, an intricate concept that unites the biological cycle of life and social unfolding imposed by the same natural cycle, responsible for continuous human ingenuity, for overcoming paradigms, for the constant substitution of centers of political, economic, religious authority and moral. Starting from these two points of reference and observing the communicational processes as key to the process, the research seeks to establish the paths traveled by humanity and its technological artifacts until the consolidation of the digital culture.